Academic executive programs in public administration and management: Some variety across Europe. Issue 1 (March 2017) - Reichard, Christoph
Universities and other higher education institutions in Europe offer a vast and increasing number of academic degree programs in the broad field of Public Administration. A subset of these programs is those offering postgraduate degrees to experienced students being already employed by public or private organisations. These executive programs are designed as long-term trainings for midcareer and executive staff and structured according to the specific demands and needs of their experienced target groups. This article provides a general picture of such academic executive programs in Europe and tries to identify common patterns and divergent features in a cross-national comparative view. It shows common trends of development over time and intends to explain observed commonalities, differences and trends by linking them to different civil service systems and state traditions.